Nabi Yesaya Teladan Kekuatan Iman dalam Masa Ujian: Menggali Pesan Nabi Yesaya dalam Analisis Makna Puasa dalam Konteks Yesaya 58:6-10 - Tamba, Gerbin; Nainggolan, Sarwedy; Siswanto, Daniel; Sinaga, Janes; Sinambela, Juita Lusiana; Beni Chandra Purba (PT. Penerbit Tiga Mutiara, 2023)
This research explores an in-depth understanding of the Prophet Isaiah's message about the strength of faith in facing times of trial, with a focus on analyzing the meaning of fasting in the context described in Isaiah 58:6-10. This research aims to understand how the Prophet Isaiah became an example of the strength of faith through the teachings of fasting, in line with his theological and contextual understanding. Text and context analysis methods are used to detail the meaning and implications of fasting in Isaiah's writings, with the aim of identifying teachings that can empower people to strengthen their faith during times of trial. It is hoped that the results of this research can contribute to practical and theological understanding of the power of faith in the context of trials, especially through understanding the message of the Prophet Isaiah about the meaning of fasting.